Understanding the Role of the Nigerian Police Force Gender Unit in Addressing Violence Against Women in Ekiti State, Nigeria - OYINLOYE, Olaoluwa Babatunde A.; AGUNBIADE, Feyisayo (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2021)
Violence against Women is one of the most widespread violations of basic human rights. Most researchers emphasize on the problem of GBV, its causes and what ought to be done in eradicating it. Although some of these suggestions such as; the creation of a Police Gender Desk among others, have been put in place, the question as to their effectiveness and whether or not they are functioning according to their mandate is yet to be answered. Objectives: the study identified the mandate of the Nigerian Police Force Gender Unit; examined the nature and dynamics of VAW cases handled by the Gender Unit of Ekiti State Police Command and examined the effectiveness and challenges of the Gender Unit of Ekiti State Police Command in handling VAW cases. Methods: The researcher employed a case study research design. The researcher interviewed a total number of 13 key informants. Content analysis and Narrative analysis were used to analyse data. Findings: It showed that there was no clearly defined mandate specifically for the Gender Unit. It was also discovered that majority of the cases were rape and defilement while domestic violence was the least reported case. This study suggested that the Gender Unit environment was not conducive for VAW cases because the survivor’s privacy was not upheld. Conclusion: The Gender Unit might not be effective on its own. The approach should be holistic and involve all actors. The response should include referring the individual survivors for specialized services such as psycho-social support, medical attention, and legal representation among others. Members of community and local system should also be sensitized for effective prevention of VAW. With the networking of all these actors, VAW would be effectively addressed. There is also need for improvements in terms of the professionalism of the officers at the Gender Unit.